Frequency of In-Hospital Outcomes in patients with Acute MI who have had a Premature Coronary Artery Disease - Muhammad Hussan Raza, Zahid Iqbal, Munir Ahmed Rashid, Abubakr Ali Saad, Amir Shehzad, Saima Dastgeer, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In underdeveloped nations like Pakistan, a recent estimate showed that the CVD deaths ratio is about 80%. This increasing prevalence of heart disease is partly due to industrial and technical advancements, which are linked to economic and social revolutions that have resulted in lifestyle changes and sedentary behavior. Aim: To determine frequency of in-hospital outcomes in patients with AMI who have had a premature coronary artery disease. Methodology; Study design; Descriptive case series. Setting; Department of Cardiology, D.G. Khan Medical College and teaching hospital, D.G.Khan.Duration; Six months.Results: The findings revealed that male patients made up 96 (66.2%) of the 145 research cases, while female patients made up 49 (33.8%). Our study participants were 47.67± 7.59 years old on average (minimum age 35 years and maximum 63 years). Before arriving at the hospital, the average time was 113.79 ± 54.36 minutes. In our research, 19(13.1%) of the individuals died, 36(24.8%) experienced post-MI angina, and 29(20%) had a cardiogenic shock. Conclusion: According to our findings, patients with early coronary artery disease and acute myocardial infarction had a significantly higher likelihood of poor clinical outcomes. Keywords: Acute myocardial infarction, mortality, and premature coronary artery disease.